Surface Strengthening Behavior of Magnesium Alloy with Laser Thermal Loading under Rapid Cooling - Ge, Y.Q.; Chen, X.; Wang, W.X.; Guo, S. (Проблемы прочности, 2018)
Laser surface strengthening had been performed on an AZ31B magnesium alloy, while the sample was rapidly cooled in liquid nitrogen. Surface strengthening behavior and mechanism were investigated. Because of strengthening mechanisms of fined grains, super solid solution, dislocation and the existence of the amorphous structure, microhardness, wear resistance and fracture toughness of magnesium alloy was greatly improved. Because of the rapid heating and cooling loading of laser, the grains of the strengthening layer were greatly refined, and amorphous structure was formed. And there were more dislocations in the strengthening layer rather than in the substrate. Furthermore, distortion of lattice caused by large numbers of Al element dissolved into α-Mg also increased the resistance to dislocation motion. Выполнено лазерное поверхностное упрочнение образца из магниевого сплава AZ31B с его одновременным быстрым охлаждением в жидком азоте. Исследованы характер и механизм поверхностного упрочнения. Благодаря механизмам уменьшения размеров зерен и возникновения твердого суперрасплава, а также их влиянию на движение дислокаций и образование аморфной структуры имеет место значительное повышение микротвердости, износостойкости и вязкости разрушения магниевого сплава. Ускоренные режимы нагрева лазером и охлаждения в жидком азоте способствовали уменьшению размеров зерен в упрочненном поверхностном слое и формированию аморфной структуры. Большинство дислокаций было обнаружено в упрочненном слое, а не в подложке. Искажение кристаллической решетки, вызванное высокой концентрацией алюминия, растворенного в α-Mg фазе, также повышает устойчивость данного сплава к движению дислокаций. Виконано лазерне поверхневе зміцнення зразка з магнієвого сплаву АZ31B з його одночасним швидким охолодженням у рідкому азоті. Досліджено характер і механізми поверхневого зміцнення. Завдяки механізмам зменшення розмірів зерен і виникнення твердого суперрозплаву та їх впливу на рух дислокацій і виникнення аморфної структури має місце значне підвищення мікротвердості, зносостійкості і в язкості руйнування магнієвого сплаву. Прискорені режими нагрівання лазером і охолодження у рідкому азоті сприяли зменшенню розмірів зерен у зміцненому поверхневому шарі і формуванню аморфної структури. Більшість дислокацій було виявлено у зміцненому шарі, а не в підкладці. Спотворення кристалічної решітки в результаті високої концентрації алюмінію, що розчиняється в α-Mg фазі, також збільшує стійкість даного сплаву до руху дислокацій